Path-Following Control Based on ALOS Guidance Law for USV - Li, Yanping; Wan, Junhe; Wang, Xiaolei; Sun, Zeqiang; Li, Hui; Yu, Zhen; Kou, Lei; Li, Junxiao; Yang, Yang (Electronics (Basel), 2025)
An adaptive line-of-sight (ALOS) guidance law with drift angle compensation is proposed to achieve the path following of unmanned surface vehicles (USVs) under the influence of ocean currents. The ALOS guidance law can calculate the desired heading of USV accurately. Compact Form Dynamic Linearization—Model-Free Adaptive Control (CFDL-MFAC) is used to control the heading. Firstly, the relationship between the path tracking error and the USV model is established. The look-ahead distance is designed as a function related to the tracking error and the speed. The sideslip angle is estimated online and compensated by using the reduced-order state observer. Finally, the heading is controlled using CFDL-MFAC, which is calculated by the ALOS guidance law. The simulation results demonstrate that satisfactory performance has been achieved of the ALOS by comparing the mean absolute error (MAE) and root mean square error (RMSE).